Advantages and Incovenients of Peritoneal Postoperatory Lavage - Fernández, Alejandro; Vispo, Alfredo Oscar; Iraola, Lidia Nora; Achaval Ayerza, Horacio (Cirugía del Uruguay, 1981)
Advantages and inconvenients of peritoneal postoperatory lavage are summarised